Environmental education in Brazil: history of the city of Sorocaba / São Paulo - Carvalho, Laura Leite de; Melo, Ismail Barra Nova de (Revista Hipótese, 2019)
This article aims to highlight the movement of Environmental Education in Brazil and the municipality of Sorocaba / São Paulo, through authors who discuss EA in this municipality, documents and laws that deal with this issue. All of them rescue important events in the diffusion of EA in Brazil and in the interior of São Paulo and reveal some of the main characters in this story. In addition, a discussion was also made about the emergence of EA over time and some concepts that define it, as well as the great importance of this theme for the community in general.
Keywords: Environmental Education; Environment; Municipality of Sorocaba